Ethnicity-stratified analysis of the association between P53 rs1042522 polymorphism and women HPV infection: A meta-analysis. (December 2021) - Si, Dan; Yao, Yanping; Chen, Xu; Qiu, Jun
Abstract: Background: Human papillomavirus (HPV) infection, especially persistent high risk HPV infection stands as the leading reason for cervical cancer morbidity. P53 protein can activate multiple tumor suppressor genes, leading to cervical cancer progression. In recent years, the relationship between P53 gene rs1042522 polymorphism and HPV infection has been investigated. However, their conclusions were contradictory and ambiguous. Objectives: The present meta-analysis is to estimate whether P53 rs1042522 polymorphism confers risk to HPV infection in cervical specimens. Methods: Relevant literatures were searched by searching databases including Pubmed, Embase, the Cochrane library, China National Knowledge Infrastructure (CNKI). Search time is from database foundation to January 2021. Results: Eight literatures were enrolled in the present meta-analysis. Positive finding between HPV infection of cervical specimens and P53 rs1042522 polymorphism was found in Brazilian population by allele contrast (Pro versus. Arg: OR = 0.52, 95%CI = 0.35–0.79), homozygote comparison (Pro/Pro versus. Arg/Arg: OR = 0.43, 95%CI = 0.20–0.94), and dominate genetic model (Pro/Pro + Arg/Pro versus. Arg/Arg: OR = 0.29, 95%CI = 0.09–0.93). The similar phenomenon was also found in Arabian population. Conclusion: We conclude that P53 rs1042522 polymorphism contributed a decreased risk to HPV infection in Brazilian and Arabian population. Highlights: TP53 rs1042522 polymorphism was significantly associated with HPV infection of Brazilian and Arabian population. This is the first meta-analysis of genetic studies on the association between HPV infection and TP53 rs1042522 polymorphism. P53 rs1042522 polymorphism contributed a decreased risk to HPV infection in Brazilian and Arabian population.